A new method and computer-controlled system for measuring the time constant of real thermoelectric modules - Ahiska, R.; Dislitas, S.; Omer, G. (Energy conversion and management, 2012)
► New method to precisely measure TE module and semiconductor parameters is developed. ► The new method is realized with a computer controlled apparatus called TEPAS. ► Fifteen different TE modules are studied with TEPAS, their parameters are obtained. ► The theoretic and experimental results validate the accuracy of new method and TEPAS. Thermoelectric and dynamic parameters of thermoelectric (TE) modules such as time constant are of crucial importance in production and utilization of these modules. Many techniques, apparatuses and software have been developed to determine the performance related parameters and time constants of TE modules; however, these techniques based on the assumption that the parameters of the semiconductors are constant or have time dependency only. Hence, the performance analyses of TE modules with these methods lack accuracy. In this study, Z, K, R and τ parameters of standard TE modules of Melcor Inc. have been acquired with a new computer controlled test system, Thermoelectric Performance Analysis System (TEPAS) which includes hardware and software based on the new method, variables of which are easily measurable temperature, current and voltage. The parameters Z, K, R and τ attained are compared with direct measurement results and the advantage of the new method and TEPAS have been demonstrated. Time constants of 15 different thermoelectric modules are calculated with the new method and three of them are attained with TEPAS. The results are compared with the other theoretical calculations and measurements available in literature. The system’s control and interface software was developed by Delphi visual programming language.